Pemanfaatan Teknologi dalam Membangun Sumber Daya Manusia di Era Bisnis Digital : Mengetahui Tantangan dan Solusinya - Inaya Amalia Putri; Munawaroh Munawaroh (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
Human resource management (HRM) is a branch of management that focuses on managing people within organizations. HRM involves selecting, developing, and retaining qualified individuals to achieve organizational goals efficiently. In the digital era, HRM faces challenges such as technological disruption and the rapid shift to automation. Modern technology has transformed training and development methods, enabling unlimited access to educational resources through online courses and digital platforms. Organizations must adapt by integrating digital tools in recruitment, training, and employee development processes to enhance efficiency and creativity. Additionally, the digital era has revolutionized business operations, enabling cost-efficient and flexible strategies through digital platforms like social media and e-commerce. However, digital transformation presents challenges, including cybersecurity threats, rapid technological changes, and digital inequality. Entrepreneurs must continuously adapt by learning new technologies, prioritizing data security, and leveraging digital solutions tailored to business needs. Digital transformation drives operational efficiency, creates new market opportunities, and enhances customer experiences, making it essential for organizations to remain competitive in a rapidly evolving landscape.